Imaging and tissue biomarkers of choline metabolism in diffuse adult glioma; 18F-fluoromethylcholine PET/CT, magnetic resonance spectroscopy, and choline kinase α - Grech-Sollars,M; Ordidge,KL; Vaqas,B; Davies,C; Vaja,V; Honeyfield,L; Camp,S; Towey,D; Mayers,H; Peterson,D; O'Neill,K; Roncaroli,F; et al. (Cancers, 2019)
The cellular and molecular basis of choline uptake on PET imaging and MRS-visible choline containing compounds is not well understood. Choline kinase alpha (ChoKa) is an enzyme that phosphorylates choline, an essential step in membrane synthesis. We investigate choline metabolism through 18F-fluoromethylcholine (18F-FMC) PET, MRS and tissue ChoKa in human glioma. 14 patients with suspected diffuse glioma underwent multimodal 3T MRI and dynamic 18FFMC PET/CT prior to surgery. Co-registered PET and MRI data were used to target biopsies to regions of high and low choline signal, and immunohistochemistry for ChoKa expression was performed. 18F-FMC/PET differentiated WHO grade IV from grade II and III tumours, whereas MRS differentiated grade III/IV from grade II tumours. Tumoural 18F-FMC/PET uptake was higher than in normal-appearing white matter across all grades and markedly elevated within regions of contrast enhancement. 18F-FMC/PET correlated weakly with MRS Cho ratios. ChoKa expression on IHC was negative or weak in all but one GBM sample, and did not correlate with tumour grade or imaging choline markers. MRS and 18F-FMC/PET provide complimentary information on glioma choline metabolism. Tracer uptake is, however, potentially confounded by blood-brain barrier permeability. ChoKa overexpression does not appear to be a common feature in diffuse glioma.